119 Enhancing lifelong learning through the role of the practice educator. (22nd November 2019) - Simpson, Gabrielle; Chapman, Geriene; Tingley, Stephanie; Fathema, Shahi; Patel, Emily
Abstract : Background: During a 6 month programme for Practice Educators (PE), discussions began surrounding how we are seen and perceived in the Trust by our staff & colleagues. It was felt that the role was unclear to the wider team and so our aim was to showcase our role to stakeholders and to publicise the necessity and positive impact of the role. Methods: Data was collected from a showcasing event to assess the perception of the tasks which is encompassed within the PE role. These were then compared to the tasks documented by PEs and demonstrated how the role is akin to an iceberg- There is much more that meets the eye. The second breakout session linked the iceberg to the impact that this has on patient safety and staff retention by using 7 broad pillars of our scope of practice. Results: The pre-course comments had very clear themes ranging from 'development & facilitation', 'essential' to a more generalised themes of 'parental ' and 'dogs body' thus showing a wide range of perceptions around the role of the Practice Educator. During our showcase comments included 'there's a lot I didn't realise you did', 'I can see your need' and 'this shouldn't be part of your role, but I can see why it is'. Post-course themes included 'demonstrated our worth' and further work needed to promote PEs – 'we need to shout about what we do and the impact'. Conclusion: The impact was clearly demonstrated in the post-course themes, from this we aim to raise further awareness by reaching a wider audience both on an internal and external platform by taking what we have learned on the development programme to further challenge perceptions of the role.